The Influence of Excellent Teller Service Based on The A3 Concept on Customer Satisfaction at PT BPR Bank Daerah Karanganyar (Perseroda) - Fadhilah Nur Hasanah; Diah Pramesti (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2024)
Competition in the banking industry drives commercial banks and BPR to improve their services, including PT BPR Bank Daerah Karanganyar (Perseroda). BPR stands for Bank Perekonomian Rakyat. Improving bank services, especially in the teller section, needs to be done to increase customer satisfaction. This research studies the effect of excellent teller service based on the concept of A3 (attitude, attention, and action) on customer satisfaction at PT BPR Bank Daerah Karanganyar (Perseroda). This study employs quantitative method, utilizing primary data collected through questionnaires distributed to 80 respondents who are the customers of PT BPR Bank Daerah Karanganyar (Perseroda). The analysis was performed using multiple linear regression. The findings indicate that the A3 variables (attitude, attention, and action) significantly influence customer satisfaction, both partially and simultaneously.